1981
DOI: 10.1113/jphysiol.1981.sp013962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Escherichia coli heat‐stable enterotoxin, cholera toxin and theophylline on ion transport in porcine colon

Abstract: SUMMARY1. The effect of heat-stable enterotoxin (ST) of Escherichia coli, cholera toxin (CT), and theophylline (a phosphodiesterase inhibitor) on ion and water transport was studied with an in vivo isolated loop system of the pig colon.2. All three agents abolished net Na absorption as a result ofa decrease in the lumen to blood Na flux alone. With all three agents, net Cl absorption was reduced, but not abolished, and net HCO3 secretion was elicited. Luminal Pco, was reduced with CT and theophylline from that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 23 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…Prior studies have demonstrated that theophylline increases cyclic AMP and cyclic GMP concentrations in pig jejunum (Argenzio & Whipp, 1981; of abolished the theophylline-induced increase in IS, (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated that theophylline increases cyclic AMP and cyclic GMP concentrations in pig jejunum (Argenzio & Whipp, 1981; of abolished the theophylline-induced increase in IS, (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Cholera toxin, the Ca2+ ionophore A23187 and theophylline, for example, stimulate Na+ and Cl-transport in pig intestinal mucosa by elevating both intracellular Ca2+ and cyclic nucleotide concentrations (Argenzio & Whipp, 1981; Argenzio, Liacos, Berschneider, Whipp & Robertson, 1984;Forsyth, Wong & Maenz, 1985;Maenz, Gabriel & Forsyth, 1987). Participation of Ca2+ in exerting ionic secretion by cholera toxin in isolated porcine enterocytes was suggested from the observation that [Ca2+]i was elevated (Maenz et al 1987), and from the increased influx of Ca2+ into jejunal brush-border membrane vesicles after addition of the toxin (Maenz & Forsyth, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…These acids could effectively lower the pH of the colon if produced in excess, however bicarbonate secretion, controlled by cellular carbonic anhydrase, ensures that colonic pH is maintained at approximately pH 7.4 (89). This balance can be effected by multiple processes, including bacteria exotoxins which can stimulate bicarbonate secretion (90), or by disease, cancer cells produce elevated levels of lactic acid and protons which modify carbonic anhydrases enabling the cancer cells to survive (19, 91). In addition to host cellular processes, environmental changes caused by switches in diet, microbial infection, or drug treatment, can cause a modulation of the microbial communities within the colon.…”
Section: Microbial Co-exposure and Mechanisms Of Colorectal Cancermentioning
confidence: 99%
“…The heat-stable enterotoxin of Escheri chia coli increases the short-circuit current (probably reflecting a rise in electrogenic Cl secretion) and mucosal cyclic GMP levels when added to rabbit caecum [68] and de creases net Na and Cl absorption in pig colon [69]. Clostridium difficile also pro duces an enterotoxin (toxin A) and a cytotoxin (toxin B) which may be partly respon sible for colonic damage in clindamycinrelated pseudomembranous colitis [70], but it is not known whether these toxins stimu late colonic secretion directly.…”
Section: Bacteria and Bacterial Toxinsmentioning
confidence: 99%